Answers

The Brainliest Answer!
2016-03-31T09:52:28+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Solutions

x sin θ - y cos θ = 0, (Given) 

⇒ x sin θ = y cos θ 

⇒ y cos θ = x sin θ

Now dividing both sides by cos θ we get, 

y = x ∙ (sin θ/cos θ) 

Again, x sin3 θ + y cos3 θ = sin θ cos θ 

⇒ x sin3 θ + x ∙ (sin θ /cos θ) ∙ cos3 θ = sin θ cos θ [Since, y = x ∙ (sin θ/cos θ)] 

⇒ x sin θ ( sin2 θ + cos2 θ) = sin θ cos θ, [since, cos θ ≠ 0] 

⇒ x sin θ (1) = sin θ cos θ,[since, sin2 θ + cos2 θ = 0] 

⇒ x sin θ = sin θ cos θ

Now dividing both sides by sin θ we get, 

⇒ x = cos θ, [since, sin θ ≠ 0] 

Therefore, y = x ∙ (sin θ/cos θ) 

⇒ y = cos θ ∙ (sin θ/cos θ), [Putting x = cos θ] 

⇒ y = sin θ 

Now, x2 + y

= cos2 θ + sin2 θ 

= 1. 

Therefore, x2 + y2 = 1.


                                                  

1 5 1
2016-03-31T18:32:21+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Given that,

x sin θ - y cos θ = 0,

⇒ x sin θ = y cos θ 

⇒ y cos θ = x sin θ

 Dividing both sides by cos θ, 

y = x ∙ (sin θ/cos θ) 

Now, x sin3 θ + y cos3 θ = sin θ cos θ 

⇒ x sin3 θ + x ∙ (sin θ /cos θ) ∙ cos3 θ = sin θ cos θ (∵ y = x ∙ (sin θ/cos θ))

⇒ x sin θ ( sin2 θ + cos2 θ) = sin θ cos θ, (∵ cos θ ≠ 0)

⇒ x sin θ (1) = sin θ cos θ,(∵ sin2 θ + cos2 θ = 0)

⇒ x sin θ = sin θ cos θ

 Dividing both sides by sin θ, 

⇒ x = cos θ, (∵ sin θ ≠ 0)

∴y = x ∙ (sin θ/cos θ) 

⇒ y = cos θ ∙ (sin θ/cos θ), (∵x = cos θ) 

⇒ y = sin θ 

Also, x2 + y2 

= cos2 θ + sin2 θ 

= 1
 
∴ x2 + y2 = 1.
0